1996
DOI: 10.1111/j.1365-2559.1996.tb01418.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of metallothionein in normal human colorectal mucosa, in adenomas and in adenocarcinomas and their associated metastases

Abstract: The immunohistochemical distribution pattern of metallothionein, a low molecular weight protein with strong affinity for divalent heavy metal ions, has been investigated in normal and neoplastic conditions of the large bowel. Utilizing a monoclonal mouse antibody the following formalin-fixed paraffin-embedded surgical or biopsy samples were studied: tubulo-villous adenomas (8 cases); adenocarcinomas with various degree of differentiation (85), nine of which were mucinous-type; synchronous tubular or tubulo-vil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
1

Year Published

1999
1999
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 27 publications
1
29
0
1
Order By: Relevance
“…However, to date, only limited information is available regarding the role of MT in colorectal carcinoma patients [13, 14, 15]. Öfner et al [13]reported that only 24% of the patients with Dukes D colon carcinoma were positive for MT and almost a similar percentage (21%) of patients were found to be positive in our patients.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…However, to date, only limited information is available regarding the role of MT in colorectal carcinoma patients [13, 14, 15]. Öfner et al [13]reported that only 24% of the patients with Dukes D colon carcinoma were positive for MT and almost a similar percentage (21%) of patients were found to be positive in our patients.…”
Section: Discussionmentioning
confidence: 82%
“…It was considered as an important mechanism during tumor progression and appears to be predominantly correlated with more advanced, highly malignant tumors [11, 12]. However, to date only limited information is available regarding the role of MT in the pathogenesis of colorectal cancer and drug resistance in colorectal cancer patients [13, 14, 15]. In the present study, we have investigated MT expression in primary colorectal tumors and their corresponding liver metastatic lesion by immunohistochemistry, and have addressed whether MT expression at these two sites could affect the prognosis and drug resistance potential with regard to cisplatin.…”
Section: Introductionmentioning
confidence: 99%
“…4) In humans, functional MT isoforms are encoded by 10 genes, 11) and their induction has been shown to be specifically regulated in a cell type-dependent manner. 12,13) Recently, MT has been detected in various types of human tumors, including breast, 14) urinary bladder, 15) testis, 16) salivary gland, 17) pancreas, 18) colon, 19) liver, 20) etc. Since it is very difficult to assess the significance of MT in urinary bladder carcinogenesis using tumor samples, we focused here on both early and late lesions induced with N-butyl-N-(4-hydroxybutyl)nitrosamine (BBN) treatment in C57BL/6 mice.…”
mentioning
confidence: 99%
“…In our study, particularly, most of the non-responding tumours (75%) also showed over-expression of MT protein. Published data and results from the present study showed low levels of MT-protein expression in colon carcinomas, especially when compared with normal colon tissue (Guiffrè et al, 1996). Most interestingly, all post-chemotherapy residual vital germ-cell tumours tested showed a decreased or still undetectable level of MT-protein expression compared with their primary tumours.…”
Section: Resultsmentioning
confidence: 73%